„Esther bevorzugt die Stille“: Vom literarischen Weiterwirken einer alttestamentlichen Frau - Langenhorst, Georg (Die Bibel in der Kunst, 2023)
The book of Esther does not belong to the favourite themes in Jewish or Christian traditions. It is ertainly not one of the most popular biblical themes in the cultural memory of literature and the arts. It stimulated, however, a huge number of dramatical sketches and plays in the premodern era. The search for modern or contemporary traces of literary reception does not bring out too many results, most oft them poems. Two lines of reception in German literature can be pointed out: First of all, Esther serves as a model for a psychological crisis between herself and her husband, the king. Rainer Maria Rilke, Gertrud Kolmar and Schalom Ben-Chorin concentrate on the moment of their meeting. The second tradition – represented by Else Lasker-Schüler, Johannes Bobrowski and Fritz Hochwälder – focuses on the political or allegorical meanings of the book of Esther, which in their conception foreshadowed the fate of the Jewish people in the 20. century. Three poems of our time finally illustrate: The productive power of the biblical figure of Esther, marginal as it might be, is still alive.